Generation Z and Islamic teachings an analytical study of intellectual and moral development in the contemporary Era - Mr. Muhammad Salman Qureshi; Mr. Muhammad Talha; Mr. Amin Ullah Khan (Journal of Religion and Society, 2026)
Generation Z, commonly defined as individuals born between 1997 and 2012, represents the first fully digital-native generation whose intellectual outlook and social behavior are significantly shaped by rapid technological advancement and digital media. While this environment provides unprecedented access to information and global connectivity, it also exposes young people to serious intellectual and moral challenges such as identity crises, materialism, misinformation, and psychological stress. In Muslim societies like Pakistan, where a large portion of the population belongs to this generation, their intellectual direction and moral development are closely linked to the future of society and the preservation of Islamic identity. This study analytically examines the intellectual and moral formation of Generation Z in the light of Islamic teachings. It highlights the relevance of key Islamic educational principles reason (Aql), moral purification (Tazkiyah), ethical conduct (Adab), and wisdom (Hikmah) as foundations for addressing contemporary challenges faced by youth. The study concludes that by integrating Islamic ethical values with modern educational approaches and digital engagement, it is possible to nurture a generation that is intellectually aware, morally responsible, and spiritually balanced in the contemporary era. Keywords: Generation Z, Islamic Teachings, Moral Development, Intellectual Development, Digital Culture, Tazkiyah, Islamic Ethics, Youth in Islam.